Characteristics Associated with Trial of Labor among Patients with Twin Pregnancies - Cipres, Danielle T.; Cowherd, Rachael B.; Barry, Olivia H.; Chen, Liqi; Yee, Lynn M. (American Journal of Perinatology, 2024)
Objective This study aimed to identify patient and provider factors associated with undergoing trial of labor (TOL) among eligible patients with twin gestations.Study Design This retrospective cohort study of patients with twin gestations who received care at a large tertiary care center from 2000 to 2016 included individuals with live pregnancies greater than 23 weeks of gestation and cephalic-presenting twin. Patients with a prior uterine scar or contraindication to vaginal delivery were excluded from analyses. Maternal and clinical characteristics were compared among patients who did and did not undergo TOL. Multivariable logistic regression models included characteristics chosen a priori and those with bivariable associations with p < 0.1. Interactions between parity and other significant variables in the primary models were also investigated.Results Among 1,888 eligible patients, 80.7% (N = 1,524) underwent TOL. Those undergoing TOL were more likely to be younger, multiparous, and have a maternal–fetal medicine physician as the delivering provider (p < 0.01). Hypertensive disorders of pregnancy were less prevalent among patients undergoing TOL (20.2 vs. 27.8%, p < 0.01). In multivariable analysis, advanced maternal age (adjusted odds ratio [aOR]: 0.55, 95% confidence interval [CI]: 0.40–0.74) and nulliparity (aOR: 0.36, 95% CI: 0.25–0.52) conferred a lower odds of TOL, while having a maternal–fetal medicine provider (aOR: 2.74, 95% CI: 1.55–4.83) was associated with higher odds. Interaction analyses demonstrated no significant interaction effects between parity and other characteristics. Among those undergoing a TOL, 76.0% (1,158/1,524) had a successful vaginal delivery of both twins, with 48.1% (557/1,158) having breech extraction of the second twin.Conclusion In this cohort of twin gestations with a high frequency of TOL, patient and provider characteristics are associated with attempting vaginal delivery. Variation in provider practices suggests differing skills and comfort with twin vaginal delivery may influence route of delivery decision-making in patients with twins.Keypoints
Keywords: breech extraction; delivery route; maternal–fetal medicine; trial of labor; twin pregnancy; vaginal delivery